2012
DOI: 10.5466/ijoms.11.46
|View full text |Cite
|
Sign up to set email alerts
|

External Apical Root Resorption and the Release of Interleukin-1 Beta in the Gingival Crevucular Fluid Treated by a Self-Ligating System

Abstract: The aim of this study was to investigate the amount of external apical root resorption (EARR) and the release of interleukin (IL)-1 beta in the gingival crevicular fluid (GCF) in subjects treated with a low-force low-friction system. Sixty patients were assigned to two groups of thirty patients each: one group received treatment with self-ligating brackets and the other received conventional ligated edgewise brackets. All patients were treated with extraction of the maxillary first premolars. The EARR of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…During the process of root resorption, previous studies have demonstrated that IL-1 beta and IL-6 are released into GCF (18,19). First, we measured the concentration of (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During the process of root resorption, previous studies have demonstrated that IL-1 beta and IL-6 are released into GCF (18,19). First, we measured the concentration of (Fig.…”
Section: Discussionmentioning
confidence: 99%